Pertimbangan Hukum Hakim Dalam Putusan Pengadilan Negeri Ambon Nomor 306/Pid.B/2020/PN.Ambon Terhadap Perampasan Jenazah Covid-19 Dalam Prespektif Tujuan Pemidanaan - Arnas, Bella Verawaty; Supusepa, Remon; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Indonesia is currently being hit by the Corona Virus or Covid-19. Various efforts have been made in handling Covid-19.Purposes of the Research: To examine and discuss the accountability of the perpetrators according to Law no. 6 of 2018 concerning Health Quarantine and To examine and discuss whether the judge's considerations in the decision of the perpetrators of the seizure of the Covid-19 corpse have fulfilled the purpose of punishment.Methods of the Research: This research is a normative juridical research type of descriptive analytical research, the sources of legal materials used in this research are primary legal materials, secondary legal materials, and tertiary legal materials. Legal materials analysis techniques are inventory procedures and identification of laws and regulations, as well as classification and systematic legal materials according to research problems, while analysis of legal materials is both destructive and qualitative methods.Results of the Research: The results obtained from this study are: Accountability of the perpetrators according to Law no. 6 of 2018 concerning Health Quarantine is criminalized and/or fined, and the judge's consideration in the decision of the perpetrators of the seizure of the Covid-19 corpse has fulfilled the purpose of punishment because it has fulfilled juridical considerations as well as non-juridical considerations. Then, in terms of the accountability of the perpetrators, more attention is paid to the teaching of participation because the confiscation of the bodies of Covid-19 is not only carried out by a few people with the participation and the judge's consideration in imposing a crime in the future will have a more deterrent effect on the perpetrators of criminal acts so that this event or incident does not happen again